TRPP2 ion channels: Critical regulators of organ morphogenesis in health and disease. (September 2017) - Busch, Tilman; Köttgen, Michael; Hofherr, Alexis
Graphical abstract: Highlights: TRPP2 is a non-selective cation channel which is part of a receptor-ion channel complex. TRPP2 localizes to primary cilia. TRPP2 is required for organ morphogenesis. Abstract: Ion channels control the membrane potential and mediate transport of ions across membranes. Archetypical physiological functions of ion channels include processes such as regulation of neuronal excitability, muscle contraction, or transepithelial ion transport. In that regard, transient receptor potential ion channel polycystin 2 (TRPP2) is remarkable, because it controls complex morphogenetic processes such as the establishment of properly shaped epithelial tubules and left-right-asymmetry of organs. The fascinating question of how an ion channel regulates morphogenesis has since captivated the attention of scientists in different disciplines. Four loosely connected key insights on different levels of biological complexity ranging from protein to whole organism have framed our understanding of TRPP2 physiology: 1) TRPP2 is a non-selective cation channel; 2) TRPP2 is part of a receptor-ion channel complex; 3) TRPP2 localizes to primary cilia; and 4) TRPP2 is required for organ morphogenesis. In this review, we will discuss the current knowledge in these key areas and highlight some of the challenges ahead.